The Effect Of Self Confidence On The Ability Of Understanding Mathematical Concepts Of Junior High School Students On The Triangle And Quarter Matter - Setiawan, Hikmal; Hendriana, Heris; Sabandar, Jozua; Fitriani, Nelly (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This research aims to analyze and study in depth about the self-confidence-influenced skills of matematiS from middle school students. The methods in this study use correlational methods with quantitative approaches. The population in this study was junior high school students in west Bandung regency and the sample of 30 people was determined by purposive sampling technique at one of the junior high schools in West Bandung Regency. Instruments in this ability in the form of comprehension ability tests as many as 5 points of questions and self-confidence scale students as many as 24 statement scales. The results of this study concluded that there is a positive influence between self-confidence and the mathematical understanding ability of middle school students. This shows that the higher the student's confidence, the higher the student's mathematical comprehension ability. Factors that affect high self-confidence include: (1) students with a high confidence attitude do not hesitate in making decisions in solving problems (2) students can have many ideas in working on the problem at hand. Meanwhile, students with less confidence will tend to have difficulty in answering potluck questions, students only memorize not yet to understand the understanding of the concept so that the student does not dare to make decisions when solving existing problems.Kata kunci: self confidence, mathematical understanding.